2011
DOI: 10.1590/s0037-86822011000200027
|View full text |Cite
|
Sign up to set email alerts
|

Rhinocerebral zygomycosis in a diabetic patient

Abstract: Rhinocerebral zygomycosis is the most frequent form of fungal infection caused by members of the Zygomycetes class. A fatal case of rhinocerebral zygomycosis caused by Rhizopus (oryzae) arrhizus with histopathological and mycological diagnosis is reported in a diabetic patient. Keywords: Zygomicosis. Diabetes mellitus. Tuberculosis. RESUMOZigomicose rinocerebral é a forma mais frequente das infecções fúngicas causadas por membros da classe Zygomicetes. É relatado um caso fatal de zigomicose rinocerebral por Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
5
4
0
Order By: Relevance
“…In agreement with our findings, there are several reports on the most common manifestations of mucormycosis in ROCM patients indicating ptosis, proptosis, periorbital swelling, facial swelling, and dysesthesia on the involved side and black necrotic area in the turbinate, palate, and other involved sites [ 1 4 , 6 , 7 , 9 , 12 , 30 , 32 ,].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our findings, there are several reports on the most common manifestations of mucormycosis in ROCM patients indicating ptosis, proptosis, periorbital swelling, facial swelling, and dysesthesia on the involved side and black necrotic area in the turbinate, palate, and other involved sites [ 1 4 , 6 , 7 , 9 , 12 , 30 , 32 ,].…”
Section: Discussionsupporting
confidence: 93%
“…In line with our study, other studies also showed that diabetes mellitus is the main underlying condition of ROCM followed by hematological disorders and transplantation due to chemotherapy causing immune defects [ 1 , 3 , 5 , 9 , 26 29 ]. In a study of 98 cases of mucormycosis in Iran, Vaezi et al [ 29 ] reported that uncontrolled diabetes was the most common underlying condition.…”
Section: Discussionsupporting
confidence: 92%
“…In line with the study by Sujatha et al in 2015, there is a change in trend towards diabetes mellitus as it is the most important factor. 11,12,13,14 Mucormycosis as the first manifestation of an undiagnosed Diabetes Mellitus 15 was the feature in 4 patients in our study as quoted byBhansali et al in her study. Also, the recent control of diabetes and diabetic ketoacidosis 11,12 was more commonly associated rather than the duration of diabetes.…”
Section: Discussionsupporting
confidence: 76%
“…11,12,13,14 Mucormycosis as the first manifestation of an undiagnosed Diabetes Mellitus 15 was the feature in 4 patients in our study as quoted byBhansali et al in her study. Also, the recent control of diabetes and diabetic ketoacidosis 11,12 was more commonly associated rather than the duration of diabetes. Recent history of admission(nosocomial infection) 16 was present in 20/37 patients which correlates with Chakrabarti et al which states that mucormycosis trend is changing towards nosocomial rather than community acquired infection.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation